Iron Pentapyridyl Complexes as Molecular Water Oxidation Catalysts: Strong Influence of a Chloride Ligand and pH in Altering the Mechanism. Issue 10 (26th April 2016) - Das, Biswanath; Orthaber, Andreas; Ott, Sascha; Thapper, Anders
Abstract: The development of molecular water oxidation catalysts based on earth‐abundant, non‐noble metals is essential for artificial photosynthesis research. Iron, which is the most abundant transition metal in the earth's crust, is a prospective candidate for this purpose. Herein, we report two iron complexes based on the polypyridyl ligand Py5OH (Py5OH=pyridine‐2, 6‐diylbis [di(pyridin‐2‐yl)methanol]) that can catalyse water oxidation to produce O2 in Ru III ‐induced (at pH 8, highest turnover number (TON)=26.5; turnover frequency (TOF)=2.2 s −1 ), Ce IV ‐induced (at pH≈1.5 highest TON=16; TOF=0.75 s −1 ) and photo‐induced (at pH 8, highest TON=43.5; TOF=0.6 s −1 ) reactions. A chloride ligand in one of the iron complexes is shown to affect the activity strongly, improve stability and, thereby, the performance at pH 8 but it inhibits oxygen evolution at pH≈1.5. The observations are consistent with a change in mechanism for catalytic water oxidation with the Fe(Py5OH) complexes between acidic (Ce IV ) and near‐neutral pH (Ru III ). Abstract : Iron man : Two iron complexes based on the polypyridyl ligand pyridine‐2, 6‐diylbis[di(pyridin‐2‐yl)methanol] (Py5OH) are reported as water oxidation catalysts in Ru III ‐induced (at pH 8), Ce IV ‐induced (at pH≈1.5), and photo‐induced (at pH 8) reactions. A change in the mechanism for water oxidation between acidic pH and near‐neutral conditions is found, and a chloride ligand in one of the iron complexes is shown to affect the activity strongly.